2023
DOI: 10.1186/s12884-023-05702-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring trends of severe postpartum haemorrhage: a hospital-based study

Abstract: Background Over the past two decades several high-income countries have reported increased rates of postpartum haemorrhage (PPH). Many of the studies are registry studies with limited access to detailed information. We aimed to explore trends of severe PPH in the largest labour ward in Norway during a 10-year period with a hospital based study. Our population constituted all women who gave birth after week 22 at Oslo University Hospital between 2008 and 2017. The main outcome measure was severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…reported a rate of 11.1% (six out of 54 deliveries in individuals with VWD in England between 1980 and 1996) when targeting VWF parameters of ≥50 IU/dL, which is similar to our rate of early PPH of 12.8% 11 . This presumed ‘lack’ of improvement may be accounted for by the fact that rates of severe PPH in the general population have been increasing over the past decades globally—even in high‐income countries with easy access to uterotonic medications 20,21 . From 2001 to 2012, the rates of PPH requiring blood transfusions increased from 1.6 to 3.8 per 1000 delivery hospitalization in the United States 20 .…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…reported a rate of 11.1% (six out of 54 deliveries in individuals with VWD in England between 1980 and 1996) when targeting VWF parameters of ≥50 IU/dL, which is similar to our rate of early PPH of 12.8% 11 . This presumed ‘lack’ of improvement may be accounted for by the fact that rates of severe PPH in the general population have been increasing over the past decades globally—even in high‐income countries with easy access to uterotonic medications 20,21 . From 2001 to 2012, the rates of PPH requiring blood transfusions increased from 1.6 to 3.8 per 1000 delivery hospitalization in the United States 20 .…”
Section: Discussionsupporting
confidence: 75%
“…From 2001 to 2012, the rates of PPH requiring blood transfusions increased from 1.6 to 3.8 per 1000 delivery hospitalization in the United States 20 . Similarly, a study in Norway found that the rate of severe PPH doubled from 17.1/1000 deliveries in 2008 to 34.2/1000 deliveries in 2017 21 . This may also explain why our study had a higher rate of early PPH when compared with earlier studies using a similar target of ≥100 IU/dL 22 .…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…This revision was prompted by the routine underestimation of blood loss during delivery [2]. In global clinical practice, there is a lack of consensus on the definition of PPH [3]. This challenges regional and national comparisons of the prevention and management of PPH [3].…”
Section: Introductionmentioning
confidence: 99%